Modelling of investment development of national economy of Ukraine on basis of regression analysis - Kuzmin, O.; Pyrog, O. (Національний університет "Львівська політехніка", 2013)
The article considers the results of modeling of investment development of national economy of Ukraine during 2001-2011 on basis of regression analysis. Determine the influence of the investment to economic development of national economy of Ukraine. Sectors of national economy divided to three groups of level of investment impact to economic development.
Keywords: modeling; investment development; national economy; Ukraine; postindustrial society; regression analysis